Demulsification efficiency of water-in-oil emulsion using non-ionic surfactants - Abdulredha, Murtada Mohammed (2019)
One of the main problems faced by the petroleum industry is growth in the presence of salty water that is accompanies crude oil productions. However, the spread of small water droplets in the oil phase produces a very stable emulsion. The contents of crude oil contribute to enhancing the stability of the water droplets dispersed in crude oil, making petroleum demulsification of emulsion more difficult and the development of a new demulsification method and desalting crude oil is necessary. Water-in-oil emulsion is very common in the petroleum industry. In this study, the chemical method used for demulsification emulsion by using surface active agents. The main objective of this study is to determine the capability of three surface-active agents as non-ionic demulsifiers, namely Propargyl Alcohol (PA), Triethylene Glycol (TG) and Glycerol (G), in breaking water-in-oil emulsion by using bottle test tube method. The eer eroh hguoin gnf nif optimal value of temperature, toluene concentration, surfactant dose, pressure and setting time on demulsification efficiency. Design Expert software was used as an approach to study the effects of five parameters on output response. Factorial designs were utilised to describe the effect of factors on the response by using the Pareto chart. The result shows that Glycerol has the highest effect on demulsification efficiency. Central Composite Design (CCD) based on Response Surface Methodology (RSM) was employed to design the experiments and establish a mathematical model for finding the optimal value for the demulsification process. The results show that the three surfactants achieved high performance in separating the water. Glycerol shows high capability compared to Triethylene Glycol and Propargyl Alcohol because the hydrophilic-lipophilic balance for Glycerol was higher than that of the other two surfactants. It was concluded from the analysis of variance (ANOVA) that the main parameters were surfactant dosage, temperature and time with highest F-values. While toluene concentration and pressure had a limited effect on breaking emulsion. Temperature played an essential role in the process of demulsification of water by reducing the viscosity of the oil and increase the kinetics energy of water droplets. Additionally, the sitting time was very important parameters in destabilizing emulsion stability through diffusing surfactant in the emulsion and adsorbing surfactant molecules on the interfacial film between two phase’s water and oil. Moreover, it was found that the maximum separation of water occurred approximately at high temperature for three models approximately above 85℃ for three surfactants. The difference between predicted R2 and adjusted R2 was reasonable for three models as well as diagnostic plots all showed that the developed models for three surfactants could adequately predict the experimental outcome. The optimal value for temperature and sitting time were approximately above 85℃ and 100min, respectively, for three models.